Mechanical Properties of Nanostructured CoCrFeNiMn High-Entropy Alloy (HEA) Coating - Dang, Chaoqun; Surjadi, James U.; Gao, Libo; Lu, Yang (Frontiers in Materials, 2018)
An equiatomic CoCrFeMnNi high-entropy alloy (HEA) thin film coating has been successfully developed by high-vacuum Radio Frequency (RF) magnetron sputtering. The deposition of a smooth and homogenous thin film with uniformly distributed equiaxed nanograins (grain size ~ 10 nm) was achieved through this technique. The thin film coating exhibits a high hardness of 6.8 ± 0.6 GPa, which is superior compared to its bulk counterpart owing to its nanocrystalline structure. Furthermore, it also shows good ductility through nanoindentation, which demonstrates its potential to serve as an alternative to traditional transition metal nitride or carbide coatings for applications in micro-fabrication and advanced coating technologies.